Politics, Finance, and the People - Reitan, Earl. author. aut Link
VIII, 278 p.
Keywords: This book traces the changes in the organization of the British economy following the War of American Independence, which unleashed a political crisis and popular movement in Britain based on demands for 'economical reform'.